Analisis Perubahan Penggunaan Lahan dan Penutupan Lahan Tahun 2003 dan 2013 di Kabupaten Dairi - Sri Wahyuni; Hardy Guchi; Benny Hidayat (Jurnal Agroekoteknologi, 2014)
The demand for land growing up synergy with population growth become one of the driving factorsof land use change. Dairi regency is one of regencies in North Sumatra with an area of 192.780hectares that most of the land not used and not optimized by the resident in order to meet thedemand for land. This study was conducted on July 2013 through March 2014 using the surveymethod with the use of GPS equipment and Landsat TM 7. The results showed that land coverconditions that primary forest, secondary forest, cultivated land, residential and open land hasincreased while the paddy fields, wet land decreased. This is due to the social conditions of thepopulation, and an increasing number of residents in the area which led to the demand of land forsettlement and cultivation of the land will continue to rise.Keywords : land cover , land use , Dairi Regency and driving factor land changes